Effects of behavioral performance, intrinsic reward value, and context stability on the formation of a higher-order nutrition habit: an intensive longitudinal diary study - Kilb, Michael; Labudek, Sarah (International journal of behavioral nutrition and physical activity, 2022)
Background: Habits drive many of our health behaviors in our daily lives. However, little is known about the relative contribution of different key factors for habit formation in real-world contexts. We examined the effects of behavioral performance, intrinsic reward value (operationalized as tastiness), and context stability on the formation of a higher-order nutrition habit. Methods: Participants were recruited via mailing lists and posts on social media platforms. N = 199 participants (Mage = 37.10 years, SD = 13.00, 86.93% female) received an online intervention for building the higher-order habit of filling half of their plates with vegetables at dinner and completed one daily online survey for up to 56 days, including the assessment of habit strength, behavioral performance, intrinsic reward value, and context stability, providing a total of N = 6352 daily measurements. N = 189 participants (N = 4175 measurements) could be included in the primary analysis. Utilizing multilevel modeling, we analyzed the impact of behavioral performance, intrinsic reward value, and context stability, as well as their interaction effects, on habit strength on the next day. Results: Habit strength significantly increased over time. This effect was strengthened in persons with high mean levels of behavioral performance. Furthermore, mean levels of behavioral performance, intrinsic reward value, and context stability were all positively related to mean levels of habit strength. There were no positive effects of daily intraindividual variations in the three examined factors on habit strength at the next day. There was an unexpected negative effect of daily behavioral performance on habit strength at the next day. We found little to no evidence for our expected and pre-registered interaction effects. In an additional exploratory analysis, there were positive effects of daily intraindividual variations in the three factors on habit strength at the same day. Conclusions: We found that behavioral performance, intrinsic reward value, and context stability were all independent predictors of habit strength of a higher-order habit at the between-person level. However, we did not find the expected associations at the within-person level. Habit interventions should promote the consistent performance of the target behaviors in stable contexts.